(untitled) (Analysis in Theory and Applications, 2017)
Let L = −∆+V be a Schrödinger operator acting on L^2(R^n), n ≥ 1, where V ot0 is a nonnegative locally integrable function on R^n. In this article, we will introduce weighted Hardy spaces H^p_L(w) associated with L by means of the square function and then study their atomic decomposition theory. We will also show that the Riesz transform ∇L^−1/2 associated with L is bounded from our new space H^p_L (w) to the classical weighted Hardy space H^p(w) when n/(n+1)< p